Responsiveness validity for measures of adjustment to life with a left ventricular assist device: Findings from the MCS A-QOL study - Elizabeth A. Hahn, MA; Larry A. Allen, MD, MHS; David Cella, PhD; David G. Beiser, MD, MS; Quin E. Denfeld, PhD, RN; James Kirklin, MD; JoAnn Lindenfeld, MD; Colleen K. McIlvennan, PhD; Bernice Ruo, MD; Jeffrey Teuteberg, MD; Michael Kiernan, MD; Liviu Klein, MD, MS; et al. (JHLT Open)
This report evaluated responsiveness validity (sensitivity to change) for five ventricular assist device (VAD)-specific patient-reported outcomes (PROs). Patients at 12 U.S. sites completed PRO measures at months 3 and 6 post-VAD including: Being Bothered by VAD, Self-care and Limitations, Self-efficacy Regarding VAD Self-care, Treatment Satisfaction, VAD Team Communication, Stigma, Kansas City Cardiomyopathy Questionnaire (KCCQ-12), EQ-5D-3L, and Intermacs Post-Implant Quality of Life Form. Statistical methods included linear mixed effect models, analysis of variance methods and Pearson correlation coefficients (r). To evaluate sensitivity to change, VAD change scores were mapped to change in indicator variables (better, no change, worse). The VAD-specific PRO measures demonstrated preliminary evidence of responsiveness to change from month 3 to month 6. Use of these measures may assist VAD clinicians to inform patients about VADs as a treatment option and identify areas of concern that may guide interventions to support adjustment to having a VAD and enhance life quality. Clinical Trial Registration: ClinicalTrials.gov ID: NCT03044535.